Endoscopic Treatment of Fluid Fistula Leak: An Analysis of 15 Cases - Pereira, Marcos Alexandre da Franca; Holanda, Maurus Marques de Almeida; Brandão, Matheus Felipe Henriques; da Costa e Souza, Rodrigo Marmo; Freitas, Samuel Navarro; Pereira, Rodrigo Baracuhy da Franca (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
Analyze the effectiveness of the endoscopic endonasal surgical technique for the management and treatment of CSF fistulas by comparing data from literature and the authors' casuistry.This is a retrospective study that included fistula leaks surgically treated by endoscopic approach between 2001 and 2020. In addition, a thorough clinical history, a complete otorhinolaryngological examination, clinical neurological evaluation, and endoscopic evaluation of the nasal cavity, are complemented by laboratory and image tests of the research's population.All 15 fistulas from the population were spontaneous and not associated with any other etiology, with most of the fistulas being in the fovea ethmoidalis and the cribriform plate. During the endoscopic approach, there were no major complications and blood loss was not reported. Only two presented recurrences of the nasoethmoidal fistula were reoperated, through the endoscopic approach, with no more recurrences reported. About their symptomatology, all patients presented with headache, rhinoliquorrhea, and neck stiffness.Based on what was presented in this article, the endoscopic surgical repair approach proved to be satisfactory as the results were in line with the literature.Level of evidence: III – retrospective cohort study.
Keywords: fluid fistula leak; endoscopic; surgery